Development of a nitrous oxide routine for the SWAT model to assess greenhouse gas emissions from agroecosystems. (March 2017) - Wagena, Moges B.; Bock, Emily M.; Sommerlot, Andrew R.; Fuka, Daniel R.; Easton, Zachary M.
Abstract: Greenhouse gas (GHG) emissions from agroecosystems, particularly nitrous oxide (N2 O), are an increasing concern. To quantify N2 O emissions from agroecosystems, which occur as a result of nitrogen (N) cycling, a new physically-based routine was developed for the Soil and Water Assessment Tool (SWAT) model to predict N2 O flux during denitrification and an existing nitrification routine was modified to capture N2 O flux during this process. The new routines predict N2 O emissions by coupling the carbon (C) and N cycles with soil moisture/temperature and pH in SWAT. The model uses reduction functions to predict total denitrification (N2 + N2 O) and partitions N2 from N2 O using a ratio method. The modified SWAT nitrification routine likewise predicts N2 O emissions using reduction functions. The new denitrification routine and modified nitrification routine were tested using GRACEnet data at University Park, Pennsylvania, and West Lafayette, Indiana. Results showed strong correlations between plot measurements of N2 O flux and the model predictions for both test sites and suggest that N2 O emissions are particularly sensitive to soil pH and soil N, and moderately sensitive to soil temperature/moisture and total soil C levels. Highlights: Nitrous oxide emissions are modeled with functional relationships between soil N, C, pH, temperature and moisture levels. The model is tested against high spatial and temporal resolution GRACEnet data at two sites. The model is particularly sensitive to soil pH and soil N levels.